1993
DOI: 10.1080/07481189308252620
|View full text |Cite
|
Sign up to set email alerts
|

Parental grief reactions and marital intimacy following infant death

Abstract: The grief reactions of bereaved mo~hers and fathers and their perception of their marital relationship following the death of their infant were examined and compared with nonbereaved couples. The correlation between bereaved parents' grief reactions and their marital intimacy was also explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 48 publications
3
78
0
2
Order By: Relevance
“…Most of the literature has focused on negative effects on social relationships suggesting declines in marital relationships and parenting after a child's death. 26,28,29,[31][32][33][34][35] Thus, it is important to also consider the assessment of positive family outcomes in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the literature has focused on negative effects on social relationships suggesting declines in marital relationships and parenting after a child's death. 26,28,29,[31][32][33][34][35] Thus, it is important to also consider the assessment of positive family outcomes in future research.…”
Section: Discussionmentioning
confidence: 99%
“…28,30 Bereaved parents have reported less marital satisfaction, less sexual intimacy, more frequent thoughts of separation, and higher divorce rates than non-bereaved parents. [31][32][33][34] Parents also may be consumed by grief and "overlook" surviving children, 35 or they may become closer and overprotective. 28 Bereaved parents have reported more parenting stress than controls, 28 and bereaved siblings have reported less communication, availability, and support from parents after the death.…”
Section: Introductionmentioning
confidence: 99%
“…Among other differences, these mothers suffered significant grief for longer periods than bereaved singleton mothers (Lang & Gottlieb, 1993;Potvin et al, 1989;Zeanah et al, 1995) and expressed more anxiety and depression. Similarly, earlier studies found that mothers and fathers of multiples did not experience significantly less grief compared with parents who had experienced the death of a singleton (Netzer & Arad, 1999;Wilson et al, 1982;Wilson et al, 1985).…”
Section: Grief and Consequences Of Bereavement For Parentsmentioning
confidence: 99%
“…However, in a tragedy that touches the entire family, the ability of family members to support one another (Dent & Stewart, 2004;Schwab, 1992), the need for support from the outside, and the significance of outside support to the parents' coping is emphasized. The death of the child is likely to affect the parents' marital relationship (Hughes & PageLieberman, 1989;Lang & Gottlieb, 1993;Samuelsson et al, 2001;Schwab, 1992Schwab, , 1998). Wood and Milo (2001) compared mothers' and fathers' stories and reported that professional support was more important for the fathers.…”
Section: Fathers' Experience Of Social Support After the Death Of A Cmentioning
confidence: 99%